Cardiovascular Disease Mortality and Non-Particulate Air Pollution: Evidence from the 20th Century - Rachel Forshaw; Natalya Kharadi; Eoin McLaughlin (Heriot-Watt University, Department of Accountancy, Economics, and Finance, 2023)
Air pollution is a global public health threat, responsible for more deaths annually than conventional lifestyle risk factors. While the link between particulate pollution and cardiovascular disease is well-established, evidence for gaseous pollutants remains limited. This study estimates the long-term population effects of a gaseous pollutant - SO2 - from 1901 to 1975 in a panel comprising 29 countries distributed globally, contributing to the under-explored literature on its cardiovascular disease mortality impact. Across a comprehensive range of empirical specifications, we observe a robust economically and statistically significant rise in cardiovascular disease mortality for an increase in SO2 emissions. We also contribute to the literature on economic growth and long-term health outcomes. Our historical perspective aligns with the call for more research on the effects of air pollution in developing nations. We highlight a complex trade-off: greater SO2 emissions increases cardiovascular disease mortality but leads to short-term regional cooling and reduced global warming and as such its abatement may contribute to future climate-related deaths.
Keywords: I15; N30; N50; Q53; Q54; Q56; 330; Air pollution; Cardiovascular disease mortality; Economic growth; Environmental Kuznets Curve; Global public health; SO2 emissions